Bear bile powder ameliorates type 2 diabetes via modulation of metabolic profiles, gut microbiota, and metabolites - Xing-Ling Chen; Ke Cai; Wen Zhang; Shu-Lan Su; Li-Hui Zhao; Li-Ping Qiu; Jin-Ao Duan (Frontiers Media S.A., 2023)
Introduction: Bear bile powder (BBP) is widely used in the clinic and has a hypoglycemic effect, but its mechanism is not clear.Methods: In this study, type 2 diabetes mellitus (T2DM) rats induced by a high-sugar and high-fat diet combined with streptozotocin were given BBP, and biochemical indexes, pathological sections, metabonomics, intestinal microbiota (IM) and short-chain fatty acids (SCFAs) were determined.Results: The results showed that BBP could reduce blood glucose, relieve inflammation, insulin resistance, and lipid metabolism disorder, and alleviate tissue damage of the liver, spleen, kidney, and pancreas in T2DM rats. It is worth noting that BBP can reverse the changes in blood and urine metabolites in T2DM rats, which are mainly related to tryptophan metabolism, pentose and glucuronate interconversions, starch and sucrose metabolism, and glycerophospholipid metabolism. In addition, BBP restored IM disorder in T2DM rats, decreased the abundance of Allobaculum, Blautia, Dubosiella, and Anaerostipes, enriched the abundance of Lactobacillus, Romboutsia, UCG-005, and norank_f__Eggerthellaceae, and increased the concentration of SCFAs in intestinal contents.Discussion: These findings suggest that BBP may improve T2DM by regulating multiple metabolic pathways, IM composition, and SCFAs levels.